Investigations on the Wear Rate of Sintering Diamond Core Bit during the Hole Drilling Process of Al2O3 Bulletproof Ceramics - Lei Zheng; Chen Zhang; Xianglong Dong; Shitian Zhao; Weidong Wu; Zhi Cui; Yaoqing Ren (Advances in Materials Science and Engineering)
Bulletproof ceramics are usually hard and brittle with high elastic modulus, high compressive strength, and low tensile strength. While machining bulletproof ceramics, severe tool wear makes it difficult to obtain desired machining quality and efficiency, especially in hole drilling. In this work, an intensive experimental study on the overall wear rate of the sintering diamond thin-wall core bit during the hole drilling of Al2O3 bulletproof ceramics (99 wt.%) has been carried out. The quality loss of the bit after each hole drilled was selected for representing the overall wear rate of the bit. Based on experimental data, the influences of the main bit performance and machining process parameters on the overall wear rate of the bit have been analyzed. According to the results discussed, under the test conditions, finer diamond grit, higher diamond concentration, lower number of water gaps, thinner wall thickness, or lower bit load all can decrease the wear rate of the bit. However, within a certain range, the spindle speed has little influence on the overall wear resistance of the bit, but when the spindle speed increases, the machining efficiency can be significantly improved. The results obtained in this work can offer a valuable reference for the use of sintering diamond thin-wall core bits in the hole drilling of bulletproof ceramics.